PERILAKU KONSUMTIF IBU RUMAH TANGGA (PERSPEKTIF SYARI’AT ISLAM) - Hj. A Sukmawati Asaad (Al-Amwal : Journal of Islamic Economic Law, 2016)
Indonesia's economic growth in the developed and developing carry capita income of Indonesia's population also increased, causing living standards increasingly prosperous population. It is affected by the person's shopping behavior patterns including housewives as a family financial management, in addition to the shopping places are comfortable and provide all the needs of consumers influence consumer behavior. In Islamic Sharia, one of the functions treasure as jewelry, treasure the jewelry world are only temporary and for that reason, as a Muslim should be able to utilize the property as well as possible to worship Allah Swt.